2018
DOI: 10.1002/pep2.24067
|View full text |Cite
|
Sign up to set email alerts
|

Disordered epitopes as peptide vaccines

Abstract: The development of clinically useful peptide‐based vaccines remains a long‐standing goal. This review highlights that intrinsically disordered protein antigens, which lack an ordered three‐dimensional structure, represent excellent starting points for the development of such vaccines. Disordered proteins represent an important class of antigen in a wide range of human pathogens, and, contrary to widespread belief, they are frequently targets of protective antibody responses. Importantly, disordered epitopes ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 106 publications
(132 reference statements)
1
29
0
Order By: Relevance
“…Even from a structural point of view, epitopes do not necessarily follow expectations. While the vast majority of them in all species and genes are composed of extracellular sites, the exposure to an outside solvent would predict a high percentage of disorder (MacRaild et al 2018). Instead, we find that, on average, ~ 30% of the epitope sites are disordered and in Haemamoeba and Vinckeia this percentage is even lower (11% in Haemamoeba and 4% in Vinckeia; Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even from a structural point of view, epitopes do not necessarily follow expectations. While the vast majority of them in all species and genes are composed of extracellular sites, the exposure to an outside solvent would predict a high percentage of disorder (MacRaild et al 2018). Instead, we find that, on average, ~ 30% of the epitope sites are disordered and in Haemamoeba and Vinckeia this percentage is even lower (11% in Haemamoeba and 4% in Vinckeia; Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of antimalarial vaccines is dependent, in part, on the quality and accessibility of the target sequence. Desirable properties in a target include (i) conservation, which supports long-term stability, (ii) accessibility, for ease of targeting, (iii) specificity, which allows sequences to be targeted uniquely, and (iv) the presence of adjuvant targets that could strengthen and refine the targeting process (MacRaild et al 2018). For the epitopes of Plasmodium species, (ii) and (iii) are relatively well known but (i) and (iv) are not.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence has shown that intrinsically disordered regions (IDRs), such as epitopes (disordered epitopes), are more enriched in linear B-cell epitopes, putative disordered binding sites, and disorder–order transitioning T cell epitopes [ 17 , 31 , 32 ]. Moreover, disordered epitopes can induce an adaptive immune response and efficient protective antibody production against pathogen surface proteins [ 18 , 33 , 34 , 35 ] due to the solvent exposure and entropic cost efficiency of the paratope–disordered epitope complex [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, a linear antigenic peptide ( 257 DKEEKE 262 ) from the stalk region of CRTAM (here referred to as IDR4) was able to induce antibodies that recognized CRTAM expressed in MDCK epithelial cells and rat kidney cells [ 37 ]. These data suggest that disordered peptides are efficient in inducing a specific immune response, as reflected by their use in vaccine development [ 17 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation